2021
DOI: 10.1177/03000605211018600
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pregnancy after intrauterine insemination in women with polycystic ovary syndrome

Abstract: Objective To evaluate the effects of body mass index (BMI) in patients with polycystic ovary syndrome (PCOS) undergoing controlled ovarian stimulation (COS) with intrauterine insemination (IUI). Methods This retrospective study evaluated couples with PCOS undergoing COS and IUI. The relationship between cumulative IUI pregnancy outcomes and BMI, treatment cycles, treatment schemes, number of dominant follicles, endometrial thickness, infertility duration and type of infertility was analysed. Results The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…World Health Organization (WHO) classification for nutritional status is defined by underweight as <18.5 kg/m 2 , normal weight as 18.5–24.9 kg/m 2 , overweight as 25.0–29.9 kg/m², and obese as BMI ≥ 30 kg/m 2 [ 2 , 33 ], and most of studies adopted this classification [ 13 , 15 , 16 , 17 , 18 , 19 , 34 , 35 , 36 ]. However, some studies used 24 kg/m 2 and 28 kg/m 2 as cut-off points for overweightness and obesity [ 37 ], respectively, especially studies conducted in China [ 12 , 14 , 20 , 21 , 38 , 39 ]. Regarding the criteria of PCOS, 15 studies used the 2003 Rotterdam criteria to diagnose PCOS, while only one study in 1992 used ultrasound images as diagnostic criteria [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…World Health Organization (WHO) classification for nutritional status is defined by underweight as <18.5 kg/m 2 , normal weight as 18.5–24.9 kg/m 2 , overweight as 25.0–29.9 kg/m², and obese as BMI ≥ 30 kg/m 2 [ 2 , 33 ], and most of studies adopted this classification [ 13 , 15 , 16 , 17 , 18 , 19 , 34 , 35 , 36 ]. However, some studies used 24 kg/m 2 and 28 kg/m 2 as cut-off points for overweightness and obesity [ 37 ], respectively, especially studies conducted in China [ 12 , 14 , 20 , 21 , 38 , 39 ]. Regarding the criteria of PCOS, 15 studies used the 2003 Rotterdam criteria to diagnose PCOS, while only one study in 1992 used ultrasound images as diagnostic criteria [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conception method in most of the studies were in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) (13 studies). Ovulation induction was used in one study [ 40 ], ovulation induction with intrauterine insemination (IUI) in one study [ 38 ], and any conception method (including spontaneous pregnancy, timed-coitus, IUI, IVF/ICSI) in one study [ 34 ]. Among IVF or ICSI studies, four studies used long protocol [ 12 , 14 , 19 , 20 ], one study applied ultra-long protocol [ 17 ], three studies were conducted with GnRH antagonist protocol [ 18 , 36 , 39 ], two studies used various protocols [ 15 , 16 ], and three studies did not mention which protocol they used [ 13 , 21 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of cancellation or conversion to IVF and IVM treatment were comparable between HA and non-HA groups. Previous studies on IUI considered factors such as age [ 21 ], obesity [ 22 ], ovulation dysfunction [ 23 , 24 ], ovarian reserve [ 21 , 25 - 27 ], and the presence of HA [ 28 ] as predictors for pregnancy. This study could not demonstrate the hypothesis that HA has a negative impact on pregnancy outcomes after OI+IUI.…”
Section: Discussionmentioning
confidence: 99%
“…High BMI could also affect OI+IUI treatment outcomes negatively. A recent retrospective study by Guan et al [ 22 ] investigating 831 IUI cycles showed that obese women might require more gonadotropin doses and more days of stimulation. Moreover, obesity is recognized in the literature as an aggravating factor of endocrine-metabolic disorders, insulin resistance, response to ovarian stimulation, and adverse events in pregnancy and the neonatal period [ 32 - 38 ].…”
Section: Discussionmentioning
confidence: 99%